Pyridine vs. Bipyridine Coordination in PtCl2 Complexes of 4‐tButyl‐4'‐(4‐pyridinyl)‐2, 2'‐bipyridine12. Issue 14 (22nd May 2013) - Rank, Matthias; Zabel, Manfred; Winter, Rainer F.
Abstract The reaction of the new terpyridine ligand 4‐tbutyl‐4'‐(4‐pyridinyl)‐2, 2'‐bipyridine L with various sources of "PtCl2" selectively yields either trans‐[PtCl2(L)2] (1) with L bonded in a monodentate fashion via its pendant 4‐pyridyl ring or cis‐[PtCl2(L)] (2), where L coordinates in a bidentate fashion through its 2, 2'‐bipyridine subunit. The molecular structures of L and of complex 1 were determined by X‐ray crystallography and exhibit intra‐ and intermolecular hydrogen bonding. We have also converted the dichloro complex 2 into the bis(coumarin thiolate) complex 3. Owing to their free imine coordination sites, complexes 1–3 constitute interesting building blocks for multimetal structures in a "complexes as ligands" approach. The reductive behaviour of L and of complexes 1–3 has been investigated by cyclic and square wave voltammetry.